(untitled) (BSAA arte, 2023)
Between 1366 and the 19th century, the town of Piedrahíta (Ávila) belonged to the House of Alba, becoming one of the heads of the Lordship of Valdecorneja. After completing its walling in the 15th century, important maintenance works were carried out throughout the following centuries, including the inevitable repairs and the opening of new portals and other minor accesses. In this article, unpublished data are provided in relation to them, clarifying the authorship and chronology of the only two accesses currently preserved. Likewise, new information is provided regarding its layout and the gradual process of deterioration and partial loss.